Myoblast seeded bovine tunica vaginalis for repair abdominal wall defects and method for preparing the same - Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Mohammed Alitheen, Noorjahan Banu; Tsedeke, Ayele Taddese (2009)
The present invention relates to a biomaterial for repair of abdominal wall defects comprising a sterile processed bovine tunica vaginalis and myoblast cells and a method for making the same. The preferred embodiment, collagen based biomaterials, which can be used for reconstruction of a abdominal wall defects for regeneration of skeletal muscle tissue in human and veterinary medicine. The present invention also provides a novel method for making/ preparing which increased the biocompatibility and shef life of the invented scaffolds, thereby following of seeding of myoblast on the bovine tunica vaginalis to improve its mechanical performances through skeletal muscle tissue engineering.